Pengaruh Faktor Sosial Ekonomi Dan Materialism pada Personal Financial Behavior melalui Financial Literacy Mahasiswa Akuntansi - Dewi, Luh Gede Krisna; Yenni Latrini, Made (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p18, 2020)
The aims of this study is to analyze and to find empirical evidence of the influence of socio-economic factors and materialism on the personal financial behavior of accounting students through their level of financial literacy. The research sample is accounting students at Bukit Jimbaran Campus determined using purposive sampling method. From the sampling process, 67 respondents completed the questionnaire. This study uses path analysis techniques (path analysis). The results of this study found that the financial literacy variable was able to mediate the relationship between the parents' socio-economic status on the pattern of personal financial behavior of accounting students. Social status and materialism attitudes also become factors that influence the level of financial literacy of students and their personal financial behavior. The implications of this research are expected to be useful for educational institutions to develop educational curricula and learning patterns related to socio-economic factors (parent status or income) and psychological factors (materialism) in influencing personal financial behavior of accounting students through the financial literacy level. Keywords: Personal Financial Behavior; Socio-Economic Factors; Materialism; Financial Literacy.